2003
DOI: 10.1172/jci200318212
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase signal transduces angiotensin II in hepatic stellate cells and is critical in hepatic fibrosis

Abstract: Angiotensin II (Ang II) is a pro-oxidant and fibrogenic cytokine. We investigated the role of NADPH oxidase in Ang II-induced effects in hepatic stellate cells (HSCs), a fibrogenic cell type. Human HSCs express mRNAs of key components of nonphagocytic NADPH oxidase. Ang II phosphorylated p47 phox , a regulatory subunit of NADPH oxidase, and induced reactive oxygen species formation via NADPH oxidase activity. Ang II phosphorylated AKT and MAPKs and increased AP-1 DNA binding in a redox-sensitive manner. Ang II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
182
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(194 citation statements)
references
References 50 publications
(34 reference statements)
11
182
1
Order By: Relevance
“…Angiotensin II stimulates nicotinamide adenine dinucleotide phosphate (NADPH) oxidase expression that induces the production of reactive oxygen species, and triggers inflammatory response. [25][26][27][28] In this study, we found that aliskiren reduced oxidative stress and IL-6 expression in non-infarcted area similarly to valsartan with our tested doses. In addition, the combination of valsartan and aliskiren further suppressed oxidative stress and IL-6 expression in non-infarcted area than either monotherapy.…”
Section: Discussionsupporting
confidence: 61%
“…Angiotensin II stimulates nicotinamide adenine dinucleotide phosphate (NADPH) oxidase expression that induces the production of reactive oxygen species, and triggers inflammatory response. [25][26][27][28] In this study, we found that aliskiren reduced oxidative stress and IL-6 expression in non-infarcted area similarly to valsartan with our tested doses. In addition, the combination of valsartan and aliskiren further suppressed oxidative stress and IL-6 expression in non-infarcted area than either monotherapy.…”
Section: Discussionsupporting
confidence: 61%
“…The hydroxyproline content in liver samples was quantified colorimetrically according to a published method. 19 Briefly, a 0.2-g liver sample was homogenized in 6 N HCl and hydrolyzed at 110°C for 16 hours. The hydrolysate was filtered, aliquots were evaporated under a vacuum, and the sediment was redissolved in 50% isopropanol.…”
Section: Methodsmentioning
confidence: 99%
“…ROS are involved in necrosis and apoptosis of hepatocytes and HSC activation [24,25]. Several major classes of free radical scavengers, such as catalase, superoxide SOD, and glutathione peroxidase (GSH-P), were investigated in various types of liver damage, and they afforded effective protection against the oxidative insults to hepatic parenchyma [26].…”
Section: Hepatic Stellate Cellsmentioning
confidence: 99%
“…High levels of ROS, from phagocytic cells, such as Kupffer cells (KC), protect the organism from external pathogens; however, lower amounts of ROS mainly from HSC actively participate in the regulation of intracellular signaling [25,27]. Platelet-derived growth factor (PDGF) is the most potent mitogen of HSC and is, therefore, likely to be an important mediator during liver fibrogenesis [28].…”
Section: Hepatic Stellate Cellsmentioning
confidence: 99%